Culture, self-esteem and menstrual hygiene management among adolescent girls in Uganda: the impact of economic and family strengthening - Flavia Namuwonge; Samuel Kizito; Vicent Ssentumbwe; Phionah Namatovu; Florence Namuli; Nhial T. Tutlam; Proscovia Nabunya; Fred M. Ssewamala (BMC Women's Health)
Abstract Background In many Sub-Saharan African countries (SSA), including Uganda, adolescent girls, especially those from low-income families, are disproportionately affected by inadequate menstrual hygiene management (MHM) facilities and supplies. This study assesses the impact of two interventions, including economic empowerment and family-strengthening interventions, on the self-esteem of adolescent girls and explores the moderating effects of cultural attitudes and menstrual hygiene knowledge. Methods We analyzed longitudinal data from a 3-arm Cluster Randomized Control Trial, Suubi4Her study, with a follow-up period of 24 months (2018–2022). A total of 1260 adolescent girls, aged 14–17 years, and living within a family were recruited from 47 schools within five geopolitical districts in Southwestern Uganda. The three study arms were: control (n = 16 schools, n = 408 students), Economic Empowerment using incentivized youth development accounts (YDA) (n = 16 schools, n = 471 students), and YDA + a family strengthening intervention that uses Multiple Family Group (MFG) meetings to address adolescent girls’ and family health and wellbeing (n = 15 schools, n = 381 students). We used mixed-effect linear regression models to assess the impact of economic empowerment on self-esteem, measured by the Rosenberg Self-Esteem Scale, and the moderation effect of menstrual hygiene knowledge, measured by a nine-item scale, and cultural attitudes, measured by self-reported school absence during menstrual periods. Results Baseline demographic characteristics indicate no statistically significant difference across the intervention arms. We found statistically significant main effects for time (χ2(2) = 102.07, p < 0.001) and intervention-time interaction effects (χ2(4) = 12.99, p = 0.011). Pairwise group comparisons at the different assessment time points showed no significant differences in self-esteem between YDA group and the control at baseline (β = 0.173 (-1.453, 1.108), p = 0.791), at 12 months (β = 0.372 (-0.893, 1.637), p = 0.565), and at 24 months (β = 0.153 (-0.904, 1.210), p = 0.777), indicating no significant effect of the YDA intervention alone on self-esteem. Similarly, no significant differences in self-esteem were found between the YDA + MFG group and the control at baseline (β=-0.299 (-1.713, 1.114), p = 0.678) and 12 months (β = 0.986 (-0.495, 2.468), p = 0.192). However, at 24-months follow-ups, the YDA + MFG group showed significantly higher self-esteem than the control (β = 1.282 (0.084, 2.480), p = 0.036). Additionally, those who reported school absenteeism due to cultural or religious reasons and received the YDA + MFG intervention reported higher self-esteem than usual care (β = 1.57 (0.07, 3.07), p = 0.004). No significant moderation by menstrual hygiene knowledge or cultural attitude was detected. Conclusion The YDA + MFG intervention and natural age progression improved self-esteem, though reliance on self-reported data may introduce bias. However, the YDA intervention alone did not significantly improve self-esteem at any assessment point.